Thus, the equation of sinusoidal function is [tex]y = sin( x - \frac{3\pi }{2} )[/tex]
Explanation:
The standard form of sine function is:
[tex]y = asin[b(x-h)] + k[/tex]
where,
a = amplitude
2π/b = period
h = phase shift
k = vertical displacement
Step wise formation of the equation:
In sine curve, the basic model is:
y = sinx
Apply a vertical stretch/shrink to get the desired amplitude:
new equation:
y = a sin x
y = 1 sinx
For k > 0, the curve y = sin kx has period 2π/ k
The period is 2. So the value of k is
2π = 2π / b
b = 1
So, the equation becomes:
y = 1 sin x
Phase shift is 3π/2. The new equation is
[tex]y = 1 sin [ 1 ( x - \frac{3\pi }{2} )]\\\\y = sin ( x - \frac{3\pi }{2})[/tex]
Vertical displacement, k = 0
So, the equation is
[tex]y = sin ( x - \frac{3\pi }{2} ) + 0\\\\y = sin ( x - \frac{3\pi }{2})[/tex]
Thus, the equation of sinusoidal function is [tex]y = sin( x - \frac{3\pi }{2} )[/tex]